Resource Allocation for Energy Efficiency in 5G Wireless Networks - D. Nguyen, Long (EAI Endorsed Transactions on Industrial Networks and Intelligent Systems, 2018)
Resource allocation is one important mission in wireless communication systems. In 5G wireless networks, it is essential that the new systems be more dynamic and wiser to simultaneously satisfy various network demands, by using new wireless technologies and approaches. To this end, resource allocation is faced with many significant challenges such as interference alignment, security attacks, or green communication. On the other hand, as one serious problem in 5G networks, the issue of energy is aected directly by the allocated resources in the system, i.e., bandwidth allocation, power control, association allocation, and deployment strategies. Consequently, together with the enhancement of spectral eÿciency performance, an emerging trend of 5G wireless networks is to approach green communication via energy eÿciency (EE) (bits/Hz/Joule), whose most significant challenge is due to its belonging to the fractional programming in the optimization field, i.e., nonconvex programming. This leaves many diÿcult tasks for improving network EE performance. In this paper, we will tackle the critical EE in 5G wireless networks.